BEST PRACTICE PEMANFAATAN QUIZIZZ SEBAGAI ASESMEN FORMATIF UNTUK MEMETAKAN PEMAHAMAN PESERTA DIDIK KELAS XI.6 SMAN 8 PEKANBARU PADA PEMBELAJARAN BAHASA INDONESIA MATERI TEKS DRAMA - Arnelia, Sindi; Fitrika, Sovia; Susanti, Eva; Febria, Rhani; Sukenti, Desi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Formative assessment is an essential component of the learning process that provides continuous feedback for teachers and students. In practice, however, teachers often find it difficult to obtain a comprehensive and accurate picture of all students' understanding quickly. This best practice article describes the experience of using Quizizz as a formative assessment instrument in Indonesian Language learning on the topic of drama texts in class XI.6 of SMAN 8 Pekanbaru during the Pre-Service Teacher Professional Education (PPG) Field Experience Program. Quizizz was used to map students' understanding based on five predetermined learning indicators. The assessment was completed by 34 students who answered 25 items consisting of multiple-choice and true-or-false questions on drama texts. The instrument was developed with reference to the five learning indicators, each represented by several items. Results based on Quizizz data show the highest average accuracy on Indicator 1 (identifying the definition and characteristics of drama texts) at 93.4% and Indicator 4 (understanding the process of writing a drama script) at 93.3%, while Indicator 5 (identifying forms of drama performance) obtained the lowest average at 79.0%. The mapping results were used by the teacher as a basis for determining follow-up actions, in the form of reinforcement for indicators not yet mastered and enrichment for indicators already mastered. This practice shows that Quizizz is effective as a formative assessment instrument that provides real-time, fast, and structured data on student understanding, thereby supporting more targeted instructional decision-making.